Engineering the Electronic Interaction between Atomically Dispersed Fe and RuO2 Attaining High Catalytic Activity and Durability Catalyst for Li‐O2 Battery. Issue 9 (22nd January 2023) - Lian, Zheng; Lu, Youcai; Zhao, Shaoze; Li, Zhongjun; Liu, Qingchao
Abstract: It is significant to develop catalysts with high catalytic activity and durability to improve the electrochemical performances of lithium‐oxygen batteries (LOBs). While electronic metal‐support interaction (EMSI) between metal atoms and support has shown great potential in catalytic field. Hence, to effectively improve the electrochemical performance of LOBs, atomically dispersed Fe modified RuO2 nanoparticles are designed to be loaded on hierarchical porous carbon shells (FeSA ‐RuO2 /HPCS) based on EMSI criterion. It is revealed that the Ru‐O‐Fe1 structure is formed between the atomically dispersed Fe atoms and the surrounding Ru sites through electron interaction, and this structure could act as the ultra‐high activity driving force center of oxygen reduction/evolution reaction (ORR/OER). Specifically, the Ru‐O‐Fe1 structure enhances the reaction kinetics of ORR to a certain extent, and optimizes the morphology of discharge products by reducing the adsorption energy of catalyst for O2 and LiO2 ; while during the OER process, the Ru‐O‐Fe1 structure not only greatly enhances the reaction kinetics of OER, but also catalyzes the efficient decomposition of the discharge products Li2 O2 by the favorable electron transfer between the active sites and the discharge products. Hence, LOBs based on FeSA‐RuO2 /HPCS cathodes show an ultra‐low over‐potential, high discharge capacity and superior durability. Abstract : Based on the electronic metal‐support interaction criterion, an atomically dispersed Fe‐modified RuO2 is designed as an efficient catalyst for Li‐O2 battery. The Ru‐O‐Fe1 structure formed in this catalyst changes the coordination environment of Ru sites and modulates the electronic structure, thus promoting the growth and decomposition of Li2 O2 and significantly enhancing the kinetics of oxygen reduction reaction/oxygen evolution reaction reaction.